1994
DOI: 10.1007/bf01755878
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of lymphatic invasion in squamous cell carcinoma (O-1N) with high potential of lymph node metastasis

Abstract: The process of lymph node metastasis was studied in an animal model (termed O-1N) that was successfully established using a metastatic tumor to the submandibular lymph node from a chemically induced squamous cell carcinoma of the hamster tongue. The model has been maintained by serial transplantation of metastatic tumors into the buccal pouch. Lymphovascular invasion of transplanted O-1N in the tongue was examined in serial histologic sections. Lymphatic vessels were distinguished from blood vessels by Masson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Clinical and animal epithelium-derived tumors usually invaded lymphatics and metastasized first to the RLNs. 10,[24][25][26] Physiologic and pathophysiologic studies provide further indirect evidence that tumor cells are more likely to invade peritumoral lymphatics than blood vessels. Lymphatic capillaries lack interendothelial tight junctions, pericytes, and basement membranes seen in blood vessels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Clinical and animal epithelium-derived tumors usually invaded lymphatics and metastasized first to the RLNs. 10,[24][25][26] Physiologic and pathophysiologic studies provide further indirect evidence that tumor cells are more likely to invade peritumoral lymphatics than blood vessels. Lymphatic capillaries lack interendothelial tight junctions, pericytes, and basement membranes seen in blood vessels.…”
Section: Discussionmentioning
confidence: 98%
“…The orderly progression of common cancers through the lymphatic system to the blood stream has also been described in animal tumor models. 10,25 Intramammary lymphatic tumor emboli were strongly correlated with RLN and systemic metastasis in breast cancer patients when regular sections were stained with hematoxylin and eosin. 8 The incidence of blood vessel invasion was reported in 4.7%, while others reported this phenomenon in 71% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against basement membrane components such as collagen type IV, fibronectin, and laminin have therefore been suggested to be useful in distinguishing blood from lymphatic microcapillaries (Barsky et al, 1983;Erhard et al, 1996;Hultberg and Svanholm, 1989;Nerlich and Schleicher, 1991;Otsuki et al, 1990;Sauter et al, 1998;Yoshizawa et al, 1994). While some authors claim that no staining for basement membrane components is observed in lymphatics, others report weak or discontinuous staining.…”
Section: Basement Membrane Componentsmentioning
confidence: 99%
“…In regard to these pathophysiological events, they have been recently rather stressed to function as matrices on which parenchymal cells are attached and express genes that are required in their particular phase of events. Their different combination of molecules may lead to a specific direction, for instance, odontogenetic processes by an enamel protein predominant composition [29,31] as well as tumor invasion processes by laminin or type-IV collagen [11,15,34]. In contrast, little attention has been paid to another function of ECM molecules as carriers for nutrient transport, which is indispensable in such tissues with a scanty vascular supply as cartilage or enamel pulp.…”
Section: Introductionmentioning
confidence: 98%